2017
DOI: 10.1016/j.actbio.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable zwitterionic sulfobetaine polymer and its conjugate with paclitaxel for sustained drug delivery

Abstract: A fully biodegradable zwitterionic polymer and the corresponding conjugate with paclitaxel (PTX) were synthesized as promising biomaterials. Allyl-functionalized polylactide (PLA) was employed as the precursor of polymer backbones. UV-induced thiol-ene reaction was conducted to conjugate thiol-functionalized sulfobetaine (SB) with the PLA-based backbone. The resulting zwitterionic polymer did not exhibit considerable cytotoxicity. A polymer-drug conjugate was also obtained by thiol-ene reaction of both thiol-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 74 publications
1
58
0
Order By: Relevance
“…Herein, we loaded doxorubicin (DOX) into the Au@TiO 2 core-shell, then grafted the zwitterionic polymer onto the NP for combined cancer therapy. As the cancer cells' metabolism and the immune response contribute to an acidity tumor microenvironment 33, 34, the zwitterionic polymers convert to a cationic state when in proximity of the tumor tissues. The cationic nature of the polymer, not only enhances cellular uptake due to the strengthened NP-cellular membrane interactions, but also inhibits the cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we loaded doxorubicin (DOX) into the Au@TiO 2 core-shell, then grafted the zwitterionic polymer onto the NP for combined cancer therapy. As the cancer cells' metabolism and the immune response contribute to an acidity tumor microenvironment 33, 34, the zwitterionic polymers convert to a cationic state when in proximity of the tumor tissues. The cationic nature of the polymer, not only enhances cellular uptake due to the strengthened NP-cellular membrane interactions, but also inhibits the cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrodynamic diameters of the prepared PO-PdNPs were smaller than that of the PEI-oleic acid micelles, which should be attributed to PdNPs located in the PEI-oleic acid micelles’ shell. The measured hydrodynamic diameters of the prepared PO-PdNPs was larger than the TEM particle size measured in the dry state [ 23 , 24 ]. Figure 4 b showed that the zeta potential of PO-PdNPs n was 21.5, 25.55, and 31.1 mV at a molar ratio of [N]:[Pd] = 75, 100, and 150, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, without detectable immune response and avoiding ABC phenomenon, zwitterionic polymers have been also identified as better biointerface material alternative PEG [11,12]. Recently, a variety of zwitterionic therapeutic nanoparticles, such as polymer-drug conjugates [13], nanogels [14], and polymeric micelles [15] have been developed. However, overcoming their less efficient tumor cell uptake is still a challenge [16].…”
Section: Introductionmentioning
confidence: 99%